2022
DOI: 10.20473/mgi.v17i3.310-319
|View full text |Cite
|
Sign up to set email alerts
|

Associations of Complementary Feeding Practice History and Protein Adequacy Level with Childhood Stunting in the Working Area of Puskesmas Bantaran in Probolinggo Regency

Abstract: Stunting is often associated with too early complementary feeding time and inadequate protein intake. The purpose of this study was to analyze the relationship between the practice of complementary feeding and the level of protein adequacy with the incidence of stunting in toddlers in the working area of Puskesmas Bantaran Probolinggo regency, East Java. Research used observational analytic with retrospective case control design. The sample were 22 stunted group and 22 non-stunted control group who met the inc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 16 publications
0
2
0
Order By: Relevance
“…This research is in line with study of (Amalia. R.) [29] which stated that the provision of complementary feeding with time, texture, portion, and frequency of complementary feeding found a relationship (p=0.002, OR=7.87) with the incidence stunting in toddlers, which means mothers who do not provide complementary feeding that do not meet WHO standards are 7.87 times more at risk of stunting [29]. Damayanti said that a good and appropriate pattern of giving complementary feeding could be seen from the age at which foods was given, the frequency of giving, the number/portion and the texture of the foods given.…”
Section: The Association Of Portion Complementary Feeding With Stuntingmentioning
confidence: 98%
“…This research is in line with study of (Amalia. R.) [29] which stated that the provision of complementary feeding with time, texture, portion, and frequency of complementary feeding found a relationship (p=0.002, OR=7.87) with the incidence stunting in toddlers, which means mothers who do not provide complementary feeding that do not meet WHO standards are 7.87 times more at risk of stunting [29]. Damayanti said that a good and appropriate pattern of giving complementary feeding could be seen from the age at which foods was given, the frequency of giving, the number/portion and the texture of the foods given.…”
Section: The Association Of Portion Complementary Feeding With Stuntingmentioning
confidence: 98%
“…10,11 A study by Limardi, et al 3 found that although there was no significant difference in dietary diversity between children with and without stunting, stunted children consumed a significantly lower proportion of flesh food and received significantly less protein from their diet. The findings of another study by Amalia, et al 12 in East Java Indonesia showed that toddlers with improper complementary feeding practices are 7.87 times more likely to be stunted, while toddlers with protein deficit had a 6.5 times higher risk of stunting.…”
mentioning
confidence: 90%
“…In order to achieve adequacy of protein intake and proper complementary feeding for the children, women should be empowered to affect access to resources and allocations. 4,12 Further longitudinal studies, monitoring, evaluation, and maintaining the continuity of the programs are still needed to ensure the sufficiency of animal protein intake, thus determining the effects of animal protein intake adequacy on linear growth in children to prevent stunting.…”
mentioning
confidence: 99%